Normas ISO más utilizadas en la gestión empresarial en Latinoamérica: análisis del periodo 2023-2025 - Tinoco Plasencia, Christian Jairo (Pontificia Universidad Católica del Perú, 2025)
The objective of this study was to establish the scientific evidence regarding the most widely used ISO standards in business management in Latin America during the period 2023-2025. The study was conducted through a documentary research approach, using a bibliographic design and a systematic review. The PRISMA methodology was employed, and the SciELO and Scopus databases were searched. One hundred and fifty scientific articles were reviewed, from which, after applying inclusion and exclusion criteria, 15 publications were selected for analysis of the topic during the period from 2023 to 2025. The findings demonstrate the frequency of ISO 9001 as the primary standard in research on quality and productivity, as well as in studies on the description and improvement of ISO 9001 in organizations. ISO 45001 and ISO 14001, related to occupational health and safety and environmental management, respectively, were also among the most frequently applied standards during the analyzed period. The study reveals that successful adoption of ISO standards requires greater technical compliance and a cultural transformation, commitment, and a strategic perspective. Significant challenges were identified, including organizational resistance to change, limited specialized training, and high implementation and certification costs, particularly for small and medium-sized organizations.

El objetivo de este estudio fue establecer la evidencia científica acerca de las normas ISO más utilizadas en la gestión empresarial en Latinoamérica durante el periodo 2023-2025. El estudio se ejecutó a través de una investigación documental, de diseño bibliográfico, basada en una revisión sistemática. En la investigación, se empleó la metodología PRISMA y se indagó en las bases de datos SciELO y Scopus. Se revisaron 150 artículos científicos, de los cuales, luego de la aplicación de criterios de inclusión y exclusión, se seleccionaron 15 publicaciones, que sirvieron para el análisis del tema en el periodo comprendido entre 2023 y 2025. Los hallazgos evidencian la frecuencia con que la norma ISO 9001 figura como estándar principal en investigaciones acerca de calidad y productividad, así como en estudios sobre la descripción y la mejora en organizaciones. Asimismo, las normas ISO 45001 e ISO 14001, referidas a la seguridad y salud y a la gestión ambiental, también se encuentran entre las más aplicadas en el lapso analizado. El estudio revela que el logro en la adopción de normas ISO necesita más cumplimiento a nivel técnico, y que requiere transformación cultural, compromiso y perspectiva estratégica. Se identificaron desafíos importantes, entre los cuales diversos autores señalan la resistencia al cambio en la organización, la escasa capacitación especializada y los elevados costos de aplicación y certificación, concretamente en pequeñas y medianas organizaciones.
Most widely used ISO standards in business management in Latin America: analysis of the period 2023-2025
Keywords: ISO; Certification; Business management; Latin america; Management systems; Digital transformation; ISO; Certificación; Gestión empresarial; Latinoamérica; Sistemas de gestión; Transformación digital; ISO; Certificação; Gestão empresarial; América latina; Sistemas de gestão; Transformação digital; https://purl.org/pe-repo/ocde/ford#5.02.04